Does Final Market Demand Elasticity Influence the Location of Export Processing? Evidence from Multinational Decisions in China. (1st October 2012) - Liu, Xuepeng; Lovely, Mary E.; Ondrich, Jan
Abstract Given the importance many developing countries attach to attracting foreign investors engaged in export‐processing activities, surprisingly little is known about the sensitivity of these investors to local wage differences and the role played by final product market conditions. Using data on 2, 884 foreign‐invested manufacturing projects in China, we estimate the importance of host province wages to firm's location choice and investigate how this sensitivity varies with demand conditions facing the industry in China's largest export market, the United States. We use the profit function to show theoretically that firms' ability to pass wage costs through to final markets matters for location choice and we test the implications of the theory using a control‐function technique for conditional logit developed by Petrin and Train. As predicted, we find that investors facing more elastic demand in the US market are more sensitive to wages across export‐processing locations. Taking both the factor intensity of the activity and final market demand elasticity into account, we find that investors producing homogenous goods, such as metals, chemicals, and food processing, are more likely to be attracted by relatively low wages than those producing differentiated goods. We also find that while OECD investors are more responsive to wage differences than are investors from Hong Kong, Taiwan and Macau, they are less likely to choose a location that has received a large share of prior foreign investment.